12, 000 years of landscape evolution in the southern White Mountains, New Hampshire, as recorded in Ossipee Lake sediments. (March 2023) - LeNoir, James; Cook, Timothy L.; Snyder, Noah P.
Abstract: Continuous records of sediment yield spanning from the late glacial through the Holocene to the present day provide an important opportunity to investigate landscape evolution over various timescales in response to a variety of natural and anthropogenic forcing mechanisms. This study investigates variations in sediment yield and landscape evolution in the 768 km 2 watershed of Ossipee Lake, New Hampshire, USA. We pair subbottom sonar observations with analyses of lacustrine sediment cores to interpret a 12, 000+ yr record of lake sedimentation in terms of changes in sediment yield and landscape evolution. Our results indicate high rates of sediment redistribution following deglaciation at 14, 500 to 12, 000 cal yr BP, followed by a period of gradually decreasing sediment yield until 9000 cal yr BP, marking the termination of the most intense period of paraglacial landscape adjustment. From 9000 cal yr BP to 1850 CE, sediment yield is highly variable and reveals a slightly increasing trend that we attribute to a dominant hydroclimatic control on erosion driven by increasing effective precipitation in the region throughout the Holocene. Despite evidence for a highly dynamic landscape and an abundance of unconsolidated glacigenic surface deposits throughout the watershed, we interpret a modest erosional impact from anthropogenic land use.